The frequency of agoraphobia and the comorbidity of major depressive disorder in panic disorder - Tahir, Diyar Hussain (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: Panic disorder (PD) is a common disabling psychiatric condition that has a considerable impact on the quality of life. This study was done to estimate the frequency of agoraphobia and the comorbidity of major depressive disorder (MDD) in PD, with related sex difference. Methods: A cross sectional descriptive study, was done on patients who consulted a private psychiatric clinic for features of PD, in Erbil city from August 2009 to August 2010. A convenient sample of 118 patients, 73 females and 45 males, having PD with or without agoraphobia were taken after giving their informed verbal consent. All patients were checked for the presence of MDD. The diagnoses were done clinically, and then checked according to the diagnostic and statistical manual of mental disorders, 4th edition, text revision (DSM-IV-TR). Results: Mean age of PD with or without agoraphobia was 31.1 years. Female to male ratio was 1.6/1. Mean age at onset was 26.3 years. Mean duration of illness was 4.4 years. Patients having PD without Agoraphobia were 81.4%, while having PD with agoraphobia were 18.6% in which the males (20%) affected more than females (17.8%). The comorbidity rate of MDD (mild to severe degree) in PD was 61% with higher males (68.9%) than females (57.5%). Conclusion: The majority of patients with PD in our sample had a comorbid MDD. Early detection and management of PD is necessary to reduce complications and improve their quality of life.